2015
DOI: 10.3389/fnins.2015.00372
|View full text |Cite
|
Sign up to set email alerts
|

The role of inflammation in schizophrenia

Abstract: High levels of pro-inflammatory substances such as cytokines have been described in the blood and cerebrospinal fluid of schizophrenia patients. Animal models of schizophrenia show that under certain conditions an immune disturbance during early life, such as an infection-triggered immune activation, might trigger lifelong increased immune reactivity. A large epidemiological study clearly demonstrated that severe infections and autoimmune disorders are risk factors for schizophrenia. Genetic studies have shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
276
3
15

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 389 publications
(307 citation statements)
references
References 111 publications
13
276
3
15
Order By: Relevance
“…Other possible contributors to LTL shortening include inflammation, oxidative stress, and certain chronic viral infections (reviewed in: Lindqvist et al, 2015). These factors may be increased in schizophrenia compared to HCs (Emiliani et al, 2014;Muller et al, 2015;Shivakumar et al, 2014). This could, in theory, result in shortened LTL, but there is only mixed evidence that these factors are differentially prevalent in men vs women with schizophrenia (Joseph et al, 2015;Kunz et al, 2011;Lee et al, 2016;Ramsey et al, 2013;Reyazuddin et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Other possible contributors to LTL shortening include inflammation, oxidative stress, and certain chronic viral infections (reviewed in: Lindqvist et al, 2015). These factors may be increased in schizophrenia compared to HCs (Emiliani et al, 2014;Muller et al, 2015;Shivakumar et al, 2014). This could, in theory, result in shortened LTL, but there is only mixed evidence that these factors are differentially prevalent in men vs women with schizophrenia (Joseph et al, 2015;Kunz et al, 2011;Lee et al, 2016;Ramsey et al, 2013;Reyazuddin et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…social behavior, spatial working memory, PPI) among TM Nrg1 mice exposed to maternal immune activation (O'Leary et al 2014). These clinical and preclinical findings are particularly relevant given evidence of an increase in pro-inflammatory cytokines in schizophrenia (Muller et al 2015) and is further supported by reports that NRG1 influences cell adhesion of immune cells (Kanakry et al 2007) and decreases the release of free radicals from microglial cells (Dimayuga et al 2003). Furthermore, a recent study (Sekar et al 2016) has highlighted complement 4 gene within the major histocompatibility complex (MHC) playing a leading role in synaptic dysregulation and risk for schizophrenia and therefore Nrg1 may act in concert with complement 4 and other genes in the MHC region to enhance risk for schizophrenia, perhaps via stimulation of proinflammatory markers that contribute to autoimmune activation of complement in the brain.…”
Section: Expression Quantitative Trait Loci (Eqtl) Studiesmentioning
confidence: 94%
“…Abnormal activation of the immune system may play an important role in the pathogenesis of schizophrenia (Fan et al, 2007a;Müller et al, 2012Müller et al, , 2015Müller, 2013;Smyth and Lawrie, 2013;Altamura et al, 2014;Horvath and Mirnics, 2014;Tomasik et al, 2014;Sperner-Unterweger and Fuchs, 2015) based on genetic, animal model, clinical markers and treatment studies (Potvin et al, 2008;Miller et al, 2011Miller et al, , 2013Fineberg and Ellman, 2013). Genetic evidence includes a recent genome-wide association study (GWAS) that has indicated a close relationship between genes regulating immune response and many schizophrenia risk genes (Schizophrenia Working Group of the Psychiatric Genomics, 2014).…”
Section: Introductionmentioning
confidence: 96%